Costing of the breeding operations for the national maize programs in Eastern and Southern Africa - Das, Biswanath; Mutiga, Samuel Kilonzo; Odiyo, Olivia; Madahana, Sammy Larry; Milić, Dragan; Sinyinda, Lubasi; Mwansa, Kabamba; Mukaro, Ronica; Chaingeni, Davison; Asea, Godfrey; Kwemoi, Daniel Bomet; Musundire, Lennin (Frontiers Media, 2025)
The Genetic Innovation Initiative on Accelerated Breeding (ABI) of The Consultative Group on International Agricultural Research (CGIAR) has been supporting the costing of breeding operations for the CGIAR-National Agricultural Research and Extension Systems-Small to Medium Enterprises (CGIAR-NARES-SME's) crop breeding networks. The aim is to help these breeding programs to accurately estimate operational costs, develop precise budgets, set appropriate service fees, and choose the best technologies for increased genetic gains. Breeding programs are being guided in using the University of Queensland's open-source breeding costing tool (UQ-BPCT). This paper outlines the costing strategy and demonstrates the tool's utility using data from national breeding programs in Uganda (NARO), Zambia (ZARI), and Zimbabwe (DR&SS). Results show that the percentage of budgets allocated to germplasm development ranged from 25% (DR&SS) to 52% (NARO), with conventional methods costing 7 to 47 times more than doubled haploids. Costs for trials varied, with ZARI spending 14% and DR&SS spending 51%. In one breeding cycle, NARO released 5 hybrid varieties, ZARI 2, and DR&SS 1. The programs can be optimized by implementing several strategies: adopting an Enterprise Breeding System, incorporating digital technologies for disease screening and phenotyping, network-based procurement of consumables, using modern breeding techniques like doubled haploids, genomic selection, and speed breeding to shorten cycles, and training personnel for more efficient resource use.